Trochlear Nerve Schwannoma with Intratumoral Hemorrhage Presenting with Persistent Hiccups: A Case Report - Hatae, Ryusuke; Miyazono, Masayuki; Kohri, Ryusuke; Maeda, Kazushi; Naito, Shinji (Journal of Neurological Surgery Reports, 2014)
Trochlear nerve schwannoma without neurofibromatosis is extremely rare. To our knowledge, only 31 surgical cases have been reported to date, and only 2 cases of trochlear nerve schwannoma with intratumoral hemorrhage have been reported. None of those cases presented with persistent hiccups. We report the case of a 44-year-old man with trochlear nerve schwannoma associated with intratumoral hemorrhage who presented with a 10-day history of persistent hiccups. Computed tomography and magnetic resonance imaging revealed a solid tumor with a 3-cm diameter and intratumoral hemorrhage in the left petroclival region that compressed the midbrain and pons. Subtotal removal of the tumor was performed via the zygomatic transpetrosal approach. Intraoperative findings revealed a tumor arising from the trochlear nerve. The histologic diagnosis was schwannoma of Antoni type A cells with intratumoral hemorrhage. Although the patient's left trochlear nerve palsy worsened temporarily, his postoperative course was uneventful. We present this rare case and discuss the mechanism underlying the patient's persistent hiccups.
Keywords: persistent hiccup; trochlear nerve schwannoma; intratumoral hemorrhage